Survival and breakthrough: A case study of evolutionary change in a state-owned enterprise - Yun-shi Liu; Chen-kung Huang; Ching-han Fang; Wei-ya Tsai; June-kune Chen (International Journal of Management, Economics and Social Sciences (IJMESS), 2015)
This study examines the processes undertaken by a state-owned enterprise to overcome limitations and successfully reverse its decline through moderate, gradual and small-scale evolutionary change. This paper utilizes the "social process research model" to analyze and record organizational changes at Jiangnan Resort, and further observes strategic countermeasures employed to address crises and successful management of organizational change. Results from our study suggest that organizational evolutionary change strategies should include institutionalization strategies, development of marketing channels, festival event marketing, placement marketing, product packaging strategies, niche market segmentation, service quality enhancement, and manpower flexibility strategies. Key factors in change management include Total Quality Management (TQM), Management by Objective (MBO), organizational members understanding of urgency and need of change, gaining support through education and communication, employee empowerment and participation, and institutionalizing change. The resulting information can serve as a reference for future qualitative research and development of strategic concepts for organizations planning to adopt evolutionary change into their companies.
Keywords: L16; L32; 330; State-owned Enterprises; organizational change and development; evolutionary change; change management; Evolutionary change strategies